The Adsorption of Cr(VI) Using Chitosan-Alumina Adsorbent - Darjito, Darjito; Purwonugroho, Danar; Ningsih, Rumiati (Chemistry Department, The University of Brawijaya, 2014)
Chitosan as adsorbent has been used widely, however it was not effective yet for metal ions adsorption in industrial scale. In acidic condition, chitosan’s active site tends to decrease. This drawback can was solved by coating of chitosan active site on alumina. This paper discloses to overcome that limitation. The charateristic of the active side was analysed by FTIR spectrometry toward vibration N-H group at 1679.15 cm-1, C=O group of oxalate at 1703.30 cm-1, and Al-O group of alumina at 924.07 cm-1. The adsorption capacity of the developed adsorbent was tester to adsorb Cr(VI) ions under various of pH value such as 1, 2, 3, 4, 5, 6, and 7. The contact time affect toward the adsorption was also reported in 20, 30, 40 50, 60, 70, and 80 minute. In addition, the concentration effects (100, 200, 300, 400, 500, and 600 ppm) was also studied. Chromium (VI) was measured using spectronic-20. Adsorption capacity was obtained at 66.90 mg/g under optimum conditions pH 2, and contact time 60 minute, respectively.